Clinical Study of Osteomyelitis and Infectious Arthritis - Okamura, Kazuyuki; Babagucti, Yasuhiro; Taniguchi, Yoshiyasu; Maki, Shinya; Hamasato, Yuujirou; Murayama, Takasi (Orthopedics & Traumatology, 1996)
Twenty patients with osteomyelitis and infectious arthritis who were treated by continuous suction irrigation were examinated. Subjects comprised 13 with chronic osteomyelitis or infectious arthritis, six infections of total joint arthroplasty cases and one case of acute osteomyelitis. The course of the infections were as follows: eight enthicillin resistent Staphylococcus aureus (MRSA) cases, five methicillin sensitive Staphylococcus aureus (MSSA), four staphylococcus epidermidis cases and three cases with other bacteria. The average irrigation period was 18.7 days. Healing was obtaind in twelve cases (60%). The infection relapsed in haef of the MRSA cases and two cases requied amputation of the infected limb. Erythrocyte segnentation rate (ESR) seems to be most useful marker of osteomyelitis and infectous arthritis.